EU Energy and Climate Policies: Challenges and Opportunities for Poland - Wojtkowska-Åodej, Grazyna (International Journal of Energy Economics and Policy, 2021)
Along with the observed in the second half of the 20th century progressing climate change and accelerating greenhouse gas emissions levels (GHG-greenhouse gases), the European Commission (EC) actively started to act, both internally and globally, against these adverse changes. This paper presents the current energy and climate policy of the European Union resulting from the long-term strategy based on developing low-carbon economy, and analyses its influence on energy transformation of the Polish economy. It contains results of analyses and assessments of the implementation process of energy and climate policy in the economy of Poland as an EU member, economic restructuring and it indicates challenges connected with the practical aspects of EU energy policy objectives implementation in the near future. The analysis is based on literature of the subject, EU strategic programming documents relating to the strategy of developing low-carbon economy in the EU, those relating to energy and climate policies, legal acts, reports and industry publications as well as Polish background documents and regulations. The analysis concerns the period between 2004 and 2017 and contains actual data obtained from EUROSTAT and GUS (Statistics Poland). Keywords: Energy Policy, Climate Policy, The European Union, Poland, Clean Energy JEL Classifications: Q48, Q58, F53 DOI: https://doi.org/10.32479/ijeep.11452